(untitled) (Foro de Educacion, 2021)
Although there is a global agenda which tends to promote early childhood education and investment in early childhood, regulations and institutions are disparate between countries, and that does not seem to be tied to social welfare levels, exclusively. After studying existing evidence on educational inequalities in Argentina and the United Kingdom, in this article we present a comparative analysis of the education system’s key components, i.e., legislation, public investment, coverage levels, professionalization, and characteristics of programs aimed at children, in relation with the per capita household income. The main findings are that schooling rates are higher in the UK than in Argentina, and social inequalities are somewhat lower. However, in both cases children who are not enrolled are concentrated in the most vulnerable households. In the UK, there is a more homogeneous and professionalized system, with official assessment and supervision, international quality standards, and notable progress in literacy, but the eligibility criteria for childcare funding does not prioritize the right of the child. Instead, it is based on parents’ labor inclusion. On the other hand, Argentina is characterized by regulatory advances and free education. However, there is insufficient supply, and informal systems are widespread among vulnerable populations, which lack guidance and supervision, and virtually provide welfare aid rather than educational services.